EVALUASI KINERJA CAMPURAN BETON ASPAL LAPIS AUS (AC-WC) MEMAKAI LIMBAH ABU-CPO SEBAGAI FILLER - Yelvi Yelvi; Mukhlis Mukhlis (Civil Engineering Departement, Andalas University, 2013)
Energy source for crude palm oil making process are usually from fry up palm fiber and nut shell for which produce ash as residue. Those residualhave never been optimally used, thus this study suggested to optimiseash of palm fiber and nut shell asfiller for asphalt mix. This study aims to evaluate impact ofadding ash of palm fiber and nut shell to asphalt mix performance in terms of it stability and durability and also to compare the performance of asphalt mixwith and without ash of palm fiber and nut shell using Marshall method. This study found that stability of asphalt mix with AB50% and AS50% ash of palm fiber and nut shell has likely increased and after reaching its maximum value, stability has steadily decreased, while its durability has gradually decreased. The highest and lowest IKS were found at asphalt mix with AB100% and AS100% respectively. KAO has gradually risen along with increase of percentage of ash of palm fiber and nut shell (5,6% KAO for AB100% and AB50% and AS50% and 5,8% KAO for AS100%). To conclude, this result showed that asphalt mix with filler using ash of palm fiber and nut shellneeds high concentrate asphalt in order to meet volumetric asphalt mix characteristic and Marshall. Keywords: ash of palm fiber and nut shell, stability , IKS.